The risk of male success and failure: How performance outcomes along with a high-status identity affect gender identification, risk behavior, and self-esteem. (March 2014) - Reinhard, Marc-André; Schindler, Simon; Stahlberg, Dagmar
Previous research has demonstrated that failure on a task may at times increase self-esteem, known as the failure-as-an-asset effect. This effect is observed when high-status group members (e.g., referring to management positions: men) show poor performance in a domain that is seen as a low-status domain—one in which the low-status group (e.g., referring to management positions: women) typically outperforms the high-status group. In line with social identity theory, in this case the poor performance leads high-status group members to a strong identification with the high-status ingroup, resulting in higher state self-esteem. However, social identity theory originally refers not only to self-evaluation, but also to the influence on individual behavior. Building on that, we predicted that if high-status group members show higher ingroup identification after negative individual feedback in a low-status domain, they should also show stronger ingroup prototypical behavior. A great deal of research has indicated that women's behavior is more risk-averse than is men's behavior. Thus, men should show riskier behavior after a poor performance on a test in which women outperform men. Two studies support our hypothesis. Men with an alleged individual low performance on a fictitious test reported riskier behavioral intentions (Experiment 1), and actually showed riskier behavior in an investment game (Experiment 2), when men were outperformed by women rather than when women were outperformed by men. The opposite pattern was found for men with an individual positive performance. As predicted, these effects were mediated by men's gender identification. Practical implications are discussed.